Water quality and the Sustainable Development Goals - Zadeh, S.M.; Drechsel, Pay; Salcedo, F. P. (2023)
Water quality plays a critical role in achieving the Sustainable Development Goals (SDGs), particularly SDG 6, which focuses on ensuring clean water and sanitation for all. This section highlights that water pollution is the second largest environmental cause of death globally, responsible for an estimated 1.8 million deaths in 2015, mostly from gastrointestinal diseases linked to contaminated drinking water and poor sanitation. Agriculture is identified as both a major cause and a victim of water pollution through excessive fertilizer and pesticide use, livestock effluent, and aquaculture discharges, which introduce persistent organic pollutants, pathogens, and emerging contaminants into water systems. The chapter underscores the relevance of SDG targets 6.3.1 and 6.3.2, which track wastewater treatment and ambient water quality, respectively, using tools such as field sampling, Earth observation, and water quality indices. Monitoring remains a major challenge, especially in low-resource settings. Approaches such as remote sensing, citizen science, and hydrological modeling are presented as alternatives to conventional testing. The chapter also explores water quality's interlinkages with other SDGs including health, food security, and ecosystem protection, and advocates strengthened national monitoring systems, data harmonization, and use of practical technologies to bridge data gaps and guide action.